CETP polymorphisms influence cholesterol metabolism but not Alzheimer's disease risk - Qureischie, Homeira; Heun, Reinhard; Lütjohann, Dieter; Popp, Julius; Jessen, Frank; Ledschbor-Frahnert, Christine; Thiele, Holger; Maier, Wolfgang; Hentschel, Frank; Kelemen, Peter; Kölsch, Heike (Brain research, 2008)
Cholesteryl ester transfer protein (CETP) is a component of the high density lipoprotein (HDL). Variations in the CETP gene may cause CETP deficiency, which is characterized by decreased mass and activity of the protein as well as altered HDL and LDL levels. We investigated the effect of three putative functional CETP polymorphisms (-1946 VNTR, C-629A and I405V) on the risk of Alzheimer's disease (AD) and on cholesterol, lathosterol and 24S-hydroxycholesterol levels in CSF and plasma of AD patients and controls. None of the investigated CETP polymorphisms or haplotypes had any effect on the risk of AD. However, we found that a three marker CETP haplotype (L/C/V) influenced CSF levels of lathosterol and 24S-hydroxycholesterol as well as plasma levels of total cholesterol in controls but not in AD patients. Our data suggest that CETP gene variations influence cerebral and peripheral cholesterol metabolism, but not AD risk.